Permalink Submitted by Charlotte on April 24, 2020

The way I see it, if there is no 'multiply' sign between the 2 and the (1+2), it acts just like if you were to have the expression 6/2x. Naturally, if x is replaced by (1+2), or (3), 2x=6, so the answer would be 1, as 6/6=1.

## Working it like algebra

The way I see it, if there is no 'multiply' sign between the 2 and the (1+2), it acts just like if you were to have the expression 6/2x. Naturally, if x is replaced by (1+2), or (3), 2x=6, so the answer would be 1, as 6/6=1.